How will Brexit affect the healthcare workforce?. (17th November 2020) - van Schalkwyk, May C I; Hervey, Tamara K; McCarey, Martha; Dayan, Mark; Barlow, Pepita; McKee, Martin
Abstract : As part of a series of briefings as we near the end of the Brexit transition period, May van Schalkwyk and colleagues look at its potential impact on NHS and social care staff